Non-invasive assessment of the effective dose of lamotrigine and topiramate for the treatment of epileptiform states in rats - Paronikyan, R. G.; Sargsyan, R. Sh; Avagyan, M. N.; Grigoryan, M. S.; Kostanyan, A. L.; Paronikyan, N. D.; Avagyan, V. M.; Vardanyan, L. S. (Èpilepsiâ i paroksizmalʹnye sostoâniâ (Online), 2019)
Aim. This study was aimed to test the instrumental complex called «Bioscope» for its ability to determine the optimal dose of the anticonvulsant drugs lamotrigine and topiramate in the treatment of epileptiform states.Materials and methods. The experiments were conducted with 40 mongrel white male rats weighing 180-220g. In total, there were 5 series of experiments where different doses of lamotrigine and topiramate were used. The integrative state of the animals (as determined with the Bioscope) was monitored, first at the baseline and then after the anti-epileptic drug administration and subsequently after the administration of corazol.Results. The Bioscope signals changed with changing doses of the anticonvulsant drugs. Low doses did not affect the integrative indicators, while the increasing doses caused these indicators to change. In dependence on the anticonvulsant drug dose, the administration of corasol either brought the integrative indicators back to the baseline or did not change them at all.Conclusion. The Bioscope instrumental complex can be used for the non-invasive evaluation of the effective dose of anticonvulsant drugs needed to suppress the epileptiform states in rats.